« J’avais peur de me faire déporter, mais j’ai demandé de l’aide » : Quand l’immigration par le parrainage se retourne contre les femmes - Ezquerro, Lorena Suelves (Anthropologica, 2020)
<span style="color: #000000; font-family: ’Open Sans’, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This study explores the effects of immigration laws on the trajectories of women who chose to immigrate to Canada via the family sponsorship program. This program, whereby family reunification is facilitated for couples in which one member resides in Quebec and the other outside of Canada, involves procedures that favour a “dependent incorporation” (<a class="ref showRefEvent" style="box-sizing: border-box; color: #002554; text-decoration: none; transition: all 0.3s ease 0s; font-weight: 600; word-break: break-word; font-family: ’Open Sans’, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;" href="https://utpjournals.press/doi/full/10.3138/anth-2018-0053#" data-rid="r070" data-reflink="_i13">Roca Girona 2009<span style="color: #000000; font-family: ’Open Sans’, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">) of the sponsored person into the destination country. Ten semi-structured interviews conducted with sponsored women in Quebec show that the process is complex and gives rise to asymmetrical power relations, sometimes even to violence, in a context of triple—legal, economic, and social—dependence.